Analisis Faktor-Faktor Yang Mempengaruhi Harga Saham Kategori Property and Real Estate di Bursa Efek Indonesia Tahun 2011 - 2014 - Hendika Darma L; Sendhang Nurseto (Universitas Diponegoro, 2016)
This research aims to identify the factors that affect stock price category of property and real estate inthe Indonesia Stock Exchange in 2011 until 2014, providing information and as a basis for decision making forthe company and investors.This type of research is explanatory. This research is used to explain the factors that influence the stockprice variable. This research uses a sample of 37 companies, that are included in the category of propeti andreal estate for 3 years listed on the Indonesia Stock Exchange and has a complete set of financial statements.The sampling technique of this research is purposive sampling. Analysis of the data used is factor analysis,correlation coefficient, determination coefficient, simple linear regression, t test, multiple linear regression, andf test.Variables analyzed using anti-image coefficients MSA with criterion variable has a value Measures OfSampling Adequacy (MSA) is more than 0.50. Of the six variables studied were PER, DER, ROE, ExchangeRate, Inflation and BI Rate, the coefficient of anti-MSA image shows the variables that have a value MeasuresOf Sampling Adequacy (MSA) is more than 0.50 PER, DER and ROE. Variable PER, DER and ROE wereanalyzed using simple linear regression and multiple linear regression.Based on the results of analysis show that in partial PER (Price Earning Ratio) has no effect on stockprices, DER (Debt To Equity Ratio) positive and significant effect on stock prices and ROE (Return On Equity)positive and significant effect on stock prices. Simultaneously PER (Price Earning Ratio), DER (Debt To EquityRatio), ROE (Return On Equity) positive and significant effect on stock prices.The conclusion of this research show DER (Debt To Equity Ratio), ROE (Return On Equity) partiallyaffect stock prices and PER (Price Earning Ratio), DER (Debt To Equity Ratio), ROE (Return On Equity)simultaneously affect the stock price category of property and real estate in the Indonesia Stock Exchange 2011to 2014. Based on these results, it can form the information and as a basis for decision making for investors andcompanies in their policy. The need for continued research by others to determine the effect of the variables thatare not included in this research. This variable is part of the company's financial ratios that affect stock pricesand require a more in-depth.